Knowledge, Attitude, and Performance of Radiographers about the Principles of Radiation Protection and Following Protective Standards in Medical Imaging Centers of Hospitals in Fasa in 2015 - Reza Alipoor; Ghazal Mousavian; Ali Abbasnezhad; Seyede Farnaz Mousavi; Gholamhasan Haddadi (Fasa University of Medical Sciences, 2015)
Background & Objectives: Although ionizing radiation is effective in the diagnosis of illnesses, it is dangerous from the perspective of protection for patients and radiographers working in radiology sections. Therefore, knowledge, understanding, and application of radiation protection can play an important role. The aim of this study is to assess the knowledge, attitude, and practice of the radiation protection principles in radiation workers in medical imaging centers and hospitals in Fasa, Fars, Iran. Materials & Methods: The present study is a cross-sectional one among all 50 radiation workers employed in radiology departments of this city. A questionnaire was the means of evaluation which contained demographic information and questions about the knowledge, attitude, and practice of radiology staff regarding the radiation protection. All of the completed questionnaires were analyzed, using SPSS19 software. Results: Radiographers' participation rate was 100%, and the mean score of knowledge, attitude, and practice of radiation workers in the field of radiation protection was 42.36, 62.4, and 48.54, respectively. Depending on the degree of their knowledge, there was no statistically significant difference between the radiographers' age, gender, and work experience, and the relationship between the following factors was not substantial. Conclusion: The results showed that by increasing the level of education, the awareness of radiation workers increases, too. To raise awareness of radiation protection for radiation workers, it is better to hold training courses.